Two new species of Begonia (Begoniaceae) from Bukit Baka Bukit Raya National Park, Kalimantan, Indonesia - Randi, Agusti; Mustaqim, Wendy A.; Kadhafi, Andi M.; Nursub’i, Firasadi; Ardi, Wisnu H. (Phytotaxa, 2025)
Two new species of Begonia were discovered during an expedition to Mount Bukit Raya, the highest peak in Kalimantan, Indonesian Borneo. Full descriptions with colour plates and distribution map are provided.